INTER-RELATIONSHIP OF BODY WEIGHT WITH LINEAR BODY MEASUREMENTS IN HISSARDALE SHEEP AT DIFFERENT STAGES OF LIFE - U. Younas; M. Abdullah; J. A. Bhatti; T. N. Pasha; N. Ahmad; M. Nasir; A. Hussain (Journal of Animal and Plant Sciences, 2013)
Determining animal live body weight (BW), linear body measurements, and their inter-relationship and correlation is imperative for determining genetic potential, breed standards, and improved breeding programs for higher meat production. Hissardale is the only fine wool sheep breed maintained in Pakistan and developed by crossing exotic Merino with a local carpet wool sheep Bikaneri. Data from 314 Hissardale sheep for body weight and linear body measurements including heart girth (HG), height at withers (HAW), body length (BL), ear length (EL), ear width (EW), neck length (NL), neck width (NW), tail length (TL), and tail width (TW) was obtained after random selection at the Livestock Experiment Station, Jahangirabad, Khanewal, Pakistan. The data was then analyzed to determine the appropriate model for estimating BW at different ages of life cycle including pre-weaned and post-weaned sheep. Animals were categorized according to their age (≤6, 7 to 12, 13 to 18, 19 to 24, and >24 mo). The BW (mean ± SD) of animals was found to be 10.87 ± 1.82, 16.40 ± 1.40, 21.04 ± 1.44, 25.57 ± 2.94 and 47.10 ± 4.41 kg in all age groups (≤6, 7 to 12, 13 to 18, 19 to 24, and >24 mo, respectively). Body weight was found to be significantly (P < 0.001) and positively correlated with HAW for all 5 age groups (0.79, 0.85, 0.67, 0.73, and 0.54, respectively), BL (0.69, 0.83, 0.53, 0.82, and 0.46, respectively) and HG (0.58, 0.85, 0.70, 0.76, and 0.42, respectively). However, the relationship between BW and other linear body measurement like EL, EW, NL, NW, TL, and TW were found significant (P < 0.05) but comparatively less correlated except for neck width in 0 to 6- and 7 to 12-mo age groups. The recorded body measurements had a strong positive correlation with BW, indicating that they can be used to estimate BW in Hissardale sheep of varying ages under field conditions.
Keywords: Hissardale sheep; live body weight; linear body measurements